Reactive vibrational excitation spectroscopy of formic acid in solid argon: Quantum yield for infrared induced trans→cis isomerization and solid state effects on the vibrational spectrum. - Maçôas, E. M. S. (2003)
Formic acid molecules are trapped in two predominant local environments (sites) when isolated in an argon matrix at 8 K. Using narrowband tunable infrared (IR) radiation, we performed site-selective excitation of various vibrational modes of the lower-energy trans conformer. For all excited modes, ranging from 7000 to 2950 cm-1, we detected site-selective isomerization to the higher-energy cis form. By measuring the IR absorption of a selected band of the cis conformer as a function of the excitation frequency, the reactive vibrational excitation (RVE) spectra were obtained. The trans→cis isomerization quantum yields for the excited modes were determined. Remarkably, very high absolute values were obtained for the quantum yield (up to 40%) at excitation energies above the reaction barrier. The efficiency of the photoinduced isomerization is essentially independent of the excited vibrational mode in a broad energy interval. Even when the excitation energy was below the reaction barrier, IR-induced rotational isomerization was observed, which indicates tunneling from the vibrationally excited trans conformer to the cis form. Using the RVE spectra, phonon sidebands were detected on the high-frequency side of the zero-phonon-line of the OH stretching mode of trans-formic acid. These weak and broad bands were not observed in the absorption spectra. Additionally, a relatively narrow band blueshifted by 6 cm-1 from the OH stretching fundamental mode was assigned to a librational satellite based on simulations using the hindered rotation model for an asymmetric top trapped in an octahedral crystal field. © 2003 American Institute of Physics. [ABSTRACT FROM AUTHOR] Copyright of Journal of Chemical Physics is the property of American Institute of Physics and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract. (Copyright applies to all Abstracts.)